HUBUNGAN ANTARA PERHATIAN ORANG TUA DALAM BELAJAR DAN KENAKALAN REMAJA PADA SISWA SMP NEGERI 29 JAKARTA SELATAN - Karina Amelia; Rahmiwati Marsinun (LPPM Institut Pendidikan Nusantara Global, 2023)
The purpose of this study was to determine the relationship between parental attention and juvenile delinquency towards the actions and behavior of adolescents in their relationships in the school or community environment. With a total population of 320 people consisting of 8 classes and each class consists of 40 students. With the sample used as many as 40 students. the results of the Linearity test are known to be the value of Sig. Deviation From Linearity (2-tailed) of 0.870 > 0.05. With the product moment correlation test with a significance value of 0.001 < 0.005. So there is a relationship between parental attention and juvenile delinquency in students of SMPN 29 Jakarta.